Formal Functions and Retrospective Reinterpretation in the First Movement of Schubert's String Quintet. (19th March 2014) - Martin, Nathan John; Vande Moortele, Steven
Abstract The first movement of Schubert's String Quintet, D. 956, is among the early nineteenth‐century repertoire's clearest examples of what Janet Schmalfeldt has called 'form as the process of becoming'. In this article we show how the governing formal principle of the movement's exposition is the conflation of distinct and typically consecutive formal functions. The result is an extraordinary chain of form‐functional overlaps, requiring the analyst to engage in a process of constant retrospective reinterpretation that ends only with the unambiguous closing group. Our aim is not only to revisit some familiar analytical questions about Schubert's Quintet from a form‐functional perspective, but also to provide a test case showing the applicability of form‐functional thinking to early nineteenth‐century music. We begin by presenting a form‐functional overview and cadential plan of the exposition and then home in on three passages that pose particular analytical challenges: the introduction/main‐theme/transition complex (bars 1–59), the transition/subordinate‐theme complex (bars 60–100) and the closing‐group/subordinate theme complex (bars 100–138). The article concludes by proposing certain ways in which Schmalfeldt's idea of retrospective reinterpretation may be further refined.